THE EFFECT OF DRINKING WATER CONTAINING ETHANOL EXTRACT OF KETAPANG (Terminalia catappa) LEAVES ON CARCASS CHARACTERISTICS, ABDOMINAL FAT, AND BLOOD CHOLESTEROL LEVELS OF BROILER CHICKENS - Amanda dwi Amelia (STOCK Peternakan, 2026)
This study aims to determine the effect of administering ethanol extract of ketapang leaves (Terminalia catappa) through drinking water on live weight, carcass weight, carcass percentage, abdominal fat, and blood cholesterol of broiler chickens. The study was conducted in September–October 2025 in a semi-closed cage of the Lampung State Polytechnic for 28 days. The material used was 60 broiler chickens strain MB 202 aged 8–28 days. The study used a Completely Randomized Design (CRD) consisting of 4 treatments and 5 replications, namely P0 (control), P1 (0.1 ml ketapang leaf extract/100 ml drinking water), P2 (0.2 ml/100 ml drinking water), and P3 (0.3 ml/100 ml drinking water). Data were analyzed using ANOVA and continued with Duncan's Test at the 5% level. The results showed that the administration of ethanol extract of ketapang leaves had a significant effect (P0.05) on live weight, carcass weight, and abdominal fat, but did not have a significant effect (P0.05) on carcass percentage and blood cholesterol. The best treatment for live weight and carcass weight was obtained in P2 with an average of 1,486 g and 1,054 g, respectively. The highest carcass percentage was obtained in P3 at 71%, but there was no significant difference between treatments. The lowest abdominal fat was obtained in P3 at 0.70%, while blood cholesterol levels were in the normal range of 208.20–228.60 mg/dl. The administration of ethanol extract of ketapang leaves has the potential to be used as a natural additive in drinking water to improve carcass performance and reduce abdominal fat in broiler chickens.